Meilė Lukšienė – inicjatorka pookupacyjnej reformy oświatowej na Litwie i twórca jej koncepcji - Barkauskaite, Marija; Tijūnelienė, Ona (Oficyna Wydawnicza ATUT - Wrocławskie Wydawnictwo Oświatowe, 2012)
The article is concerned with the ideas of Meilė Lukšienė (1913–2009) – an eminent scholar of the history of Lithuanian science, education, and literature, a social activist, the initiator of the educational reform - on the relations between education and culture. An overview of works written at the turn of the XXI century as well as during the occupation and after is provided and emphasis is placed on the notions that Meilė Lukšienė promoted. One of them is - a nation has a right to exist, persist, and construct its existence according to democratic standards. Th e aforementioned idea is connected with a number of the following ones - a free and honest individual should grow up in their native culture and in a natural way while gaining experience, learning of the values common to all of humanity and of the cultures of other nations. As preservation of culture is the basis of the existence of a nation and the curriculum of Lithuanian schools that prepare the youth for adult life should be integrated.
Keywords: Meilė Lukšienė; szkoła; edukacja; reforma oświatowa; Litwa